Design of Dual Mode RFID Antenna for Inventory Management and IV Fluid Level Warning System - Ssu-Han Ting; Chih-Kuang Wu; Ching-Hsing Luo (International Journal of Antennas and Propagation)
Radio frequency identification (RFID) readers are powered RF devices that communicate with an RFID tag to read necessary information. Using this capability, a dual use system for short distance inventory management and moderate distance automatic warning system for low intravenous (IV) fluid levels is designed. The RFID is affixed on the IV drip bag; the fluid in bag affects the antenna transmission distance by fluid dielectric conditions. This allows for two different operational modes (moderate and short distance). For pharmaceutical management, a handheld RFID reader can be used for short distance application. Another stationary RFID system can serve as a warning system for long distance application such as hospital care.